Effects of Physical Activity and Restricted Energy Intake on Chemically-Induced Mammary Carcinogenesis() - Jiang, Weiqin (Cancer Prev Res (Phila), 2009)
In the field of energetics and cancer, little attention has been given to whether energy balance directed interventions designed to regulate body weight by increasing energy expenditure versus reducing energy intake have an equivalent impact on the development of breast cancer. The objective of this experiment was to determine the effects on mammary carcinogenesis of physical activity (PA), achieved via running on an activity wheel, or restricted energy intake (RE). Food intake of PA and RE rats was controlled so that both groups had the same net energy balance determined by growth rate, that was 92% of the sedentary control group (SC). A total of 135 female Sprague Dawley rats were injected with 1-methyl-1-nitrosourea (50 mg/kg) and 7 days thereafter were randomized to either SC, PA, or RE. Mammary cancer incidence was 97.8%, 88.9% and 84.4% and cancer multiplicity was 3.66, 3.11, and 2.64 cancers/rat in SC, RE, and PA, respectively (SC vs. PA, p=0.02 for incidence and p=0.03 for multiplicity). Analyses of mammary carcinomas revealed that cell proliferation associated proteins were reduced and caspase 3 activity and pro-apoptotic proteins were elevated by PA or RE relative to SC (p<0.05). It was observed that these effects may be mediated, in part, by activation of AMP-activated protein kinase and down regulation of protein kinase B and the mammalian target of rapamycin.